Theoretical study of absorbed energy by empty and foam-filled composite tubes under lateral compression. (May 2017) - Elahi, Seyed Ali; Rouzegar, Jafar; Niknejad, Abbas; Assaee, Hassan
Abstract: This paper is an attempt for introduction of new theoretical relations in order to predict energy absorption behavior of empty and polyurethane foam-filled composite tubes, which are made of woven fiber fabrics, during lateral compression between two rigid plates. Such theoretical relations can be used to specify portion of different deformations that are happened during crushing process in total energy absorption of the structures. Knowing these data may help the designers to reinforce the energy absorbers more effectively. Also, several experiments are conducted on empty and polyurethane foam-filled circular E-glass/Vinylester composite tubes in order to validate the theoretical relations. The specimens are laterally compressed between two rigid plates during a quasi-static process. According to experimental studies, the composite tubes collapse with different modes of deformation during lateral flattening. Different relations are introduced for prediction of the absorbed energy of tubes with different deformation modes. The theoretical and experimental energy-displacement diagrams and total absorbed energy by the composite tubes are compared and good agreements are found. Finally, theoretical relations are compared with each other and effects of different energy absorption mechanisms on total energy absorption are discussed based on the presented relations. Highlights: This paper studies flattening of circular E-glass/vinylester tubes, theoretically. Two kinds of composite tubes are investigated: empty and polyurethane foam-filled. Experiments are conducted on composite structures to validate the theories. Reasonable agreement was obtained between theoretical and experimental results. Effect of each energy absorption mechanism on total energy absorption is studied.